Roadmap toward energy‐positive upfront nitrogen removal process in baseload LNG plant - Mkacher, Hajer; AlMomani, Fares; Pal, Ajinkya; Karimi, Iftekhar A.; Al‐musleh, Easa I. (International journal of energy research, 2022)
Summary The use of liquefied natural gas (LNG) has grown over the last decade owing to an increase in the global energy demand. This work presents a pioneering approach for rigorous simulation of an actual cold section of an LNG plant and provides a potential process optimization to achieve a higher production rate (PR) while reducing the specific power consumption (SPC). The concept of upfront nitrogen removal (UNrem) from the natural gas (NG) feed was introduced, and the impact on the PR and SPC was presented. We considered seven scenarios with varying percentages of UNrem and compared them with the conventional plant design (base case) while maintaining the product specifications (LNG high heating value [HHV] of 1105 Btu/Scf and NGL reid vapor pressure [RVP] of 2042 psia). The results show that UNrem of 87.5% from the NG feed can reduce the total power requirements by 0.24%, increase the production flow rate by 4.4%, and decrease the exergy losses by 0.23% compared with the base case. The UNrem can also have a significant improvement on the plant capacity without the need for structural modifications in the cold section. Future research should focus on the efficiency and feasibility of different UNrem processes as well as examine the use of a large‐scale system. This present study highlights for the first time the importance of upfront nitrogen removal (UNrem) in improving the production rate of liquefied natural gas (LNG) plant and reducing energy requirements. For a realistic result, the study was performed using an actual LNG plant operating conditions The process optimization is conducted by taking the benefit of the refrigerant cooling capacity while maintain the LNG purity within the international specifications. For the newly developed process, the need for retrofitting or changes within the LNG process and the overall exergy analysis were performed and compared with the base case to provide insights into the achieved improvements.